PENGARUH PRESSURE TERHADAP KECURANGAN LAPORAN KEUANGAN - Riska Adi Putri, (2021)
This study aims to determine the effect of pressure on fraudulent financial statements in 38 property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research is a type of quantitative research using secondary data in the form of annual reports and company financial statements. Common Effect Model (CEM) with panel data regression was used in this study using STATA version 16. Based on the test results and analysis it can be concluded that financial stability, external pressure, and financial target has no effect on fraudulent financial statements. Keywords: Financial Stability, External Pressure, Financial Target, Fraudulent Financial Statements.